Obtaining Informed consent: psychiatric nurses’ knowledge and practice at Federal Neuro-Psychiatric Hospital Enugu, Nigeria - Ezeruigbo, Chinwe S. F.; Osuchukwu, Easter; Elom, Michael O.; Vincent, Chinelo; Ubochi, Nneka; Iheanacho, Peace (Acta Bioethica, 2022)
Background: Within a psychiatric care setting, informed consent is the voluntary acceptance of a plan for medical care by a competent patient after full disclosure of the care plan, its risks, benefits, and alternative approaches. This implies that the patient must have full information about any treatment options and must be competent to make the needed decisions. Objective: To assess psychiatric nurses’ knowledge and practices of obtaining informed consent. Research Method: The study used a quantitative, descriptive cross-sectional survey design. Data were collected from a random sample of 99 nurses selected from a total of 131 nurses of different professional cadres working in the hospital, by means of a structured questionnaire constructed by the researchers. Data were analyzed using descriptive statistics. Results: Respondents’ score on Knowledge of Informed Consent was above average (15.06 ± 2.671 out of a possible total score of 25). Likewise, their score on the disclosure of full information to psychiatric patients before treatment was well above average (6.01 ± 2.198 out of a maximum possible score of 8). However, respondents’ score on the practice of obtaining Informed Consent was below average (2.41 ± 0.940 out of a maximum possible score of 5). Conclusion: Though a majority of the participants indicated good knowledge of informed consent, there was no corresponding correct practice of obtaining informed consent from patients in the hospital.